2019
DOI: 10.15835/nbha47311466
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ammonium to Nitrate Ratio on the Growth and Nutritional Status of Kale

Abstract: The effect of four NH4:NO3 ratios in the nutrient solution (0:100; 25:75; 50:50 and 75:25) on growth and nutrient concentrations of four kale (Brassica oleraceae L. var. acephala) hybrids: ‘CN KAL 1029’, ‘Redbor’, ‘Winnetou’, ‘Reflex’ and  one indigenous cultivar: ‘Ntopia Mytilinis’ was investigated. In the first four weeks of cultivation none of the NH4/NO3 ratios applied induced adverse effects on most growth characteristics determined whereas plants grown with 75% NH4-N accumulated higher leaf N, P, K, Fe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…(2020) reported a higher chlorophyll concentration in lettuce seedlings exposed to an NH 4 + :NO 3 - ratio 25:75 than both 100:0, 50:50 and 0:100. Studies of other species also show varying results, for example, an increase in chlorophyll content with increasing NH 4 + :NO 3 - ratios was not discovered in kale ( Assimakopoulou et al., 2019 ). Different theories are proposed to explain an increased chlorophyll content as a response to high ammonium.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) reported a higher chlorophyll concentration in lettuce seedlings exposed to an NH 4 + :NO 3 - ratio 25:75 than both 100:0, 50:50 and 0:100. Studies of other species also show varying results, for example, an increase in chlorophyll content with increasing NH 4 + :NO 3 - ratios was not discovered in kale ( Assimakopoulou et al., 2019 ). Different theories are proposed to explain an increased chlorophyll content as a response to high ammonium.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al (2021) demonstrated that lettuce and cabbage chlorophyll content was higher in plants exposed to an NH 4 + :NO 3 ratio of 50:50, than both 0:100 and 100:0, while Zhu et al ( 2020) reported a higher chlorophyll concentration in lettuce seedlings exposed to an NH 4 + :NO 3 ratio 25:75 than both 100:0, 50:50 and 0:100. Studies of other species also show varying results, for example, an increase in chlorophyll content with increasing NH 4 + :NO 3 ratios was not discovered in kale (Assimakopoulou et al, 2019). Different theories are proposed to explain an increased chlorophyll content as a response to high ammonium.…”
Section: O 2 Productionmentioning
confidence: 98%
“…La mayor concentración de Mn se obtuvo en la relación 25:75 y la menor concentración con la relación 75:25. Estos resultados concuerdan con lo reportado por Assimakopoulou et al (2019), en col rizada (Brassica oleraceae L. var. Acephala) las cuales acumularon una mayor concentración de Zn, Mn y Cu, con la aplicación de una solución con 75% de NH 4 + .…”
Section: Concentración De Micronutrientes En Hojaunclassified